2015
DOI: 10.1007/s00253-015-7047-6
|View full text |Cite
|
Sign up to set email alerts
|

The blue-light receptor CmWC-1 mediates fruit body development and secondary metabolism in Cordyceps militaris

Abstract: Light is an essential factor for pigment formation and fruit body development in Cordyceps militaris, a well-known edible and medicinal fungus. Cmwc-1, a homolog of the blue-light receptor gene white collar-1 (wc-1) in Neurospora crassa, was cloned from the C. militaris genome in our previous study. Here, Cmwc-1 gene inactivation results in thicker aerial hyphae, disordered fruit body development, a significant reduction in conidial formation, and carotenoid and cordycepin production. These characteristics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
86
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 58 publications
10
86
3
Order By: Relevance
“…Light is a necessary condition for the production of C. militaris fruiting bodies and pigments [18]. The Cmfhp gene of C. militaris was significantly upregulated after being treated with light.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Light is a necessary condition for the production of C. militaris fruiting bodies and pigments [18]. The Cmfhp gene of C. militaris was significantly upregulated after being treated with light.…”
Section: Discussionmentioning
confidence: 99%
“…Although three types of geranylgeranyl diphosphate synthase genes in C. militaris were cloned, their functions have yet to be identified [36]. It is noteworthy that the other two key enzymes (phytoene synthetase and phytoene dehydrogenase) were not found in the genome of C. militaris [13,18]. The induction of carotenoids was completely different between C. militaris and Neurospora crassa [13,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although fruiting structures are distinct between Ascomycota and Basidiomycota, they are two closely related phyla separated only for about 500 million years ago (Berbee and Taylor, 2010;Oberwinkler, 2012). Two phyla share some common regulatory mechanisms in fruiting body development, including the blue light receptor WC-1 (Linden et al, 1997;Terashima et al, 2005;Ohm et al, 2013;Yang et al, 2016), the pheromone signaling (Debuchy et al, 2010;Raudaskoski and Kothe, 2010) and the heterotrimeric G-protein complex (Lengeler et al, 2000;Brown and Casselton, 2001;Li et al, 2007). Our study revealed that CPC-2 proteins also mediate fruiting body development in both phyla.…”
Section: Discussionmentioning
confidence: 62%